Noise conversion from pump to the passively mode-locked fiber lasers at 1.5 μm - Wu, Kan (2013)
We characterize the noise conversion from the pump relative intensity noise (RIN) to the RIN and phase noise of passively mode-locked lasers at 1.5 μm. Two mode locking mechanisms, nonlinear polarization rotation (NPR) and semiconductor saturable absorber mirror (SESAM), are compared for noise conversion for the first time. It is found that the RIN and the phase noise of both types of lasers are dominated by the noise converted from the pump RIN and thus, can be predicted with the measured pump RIN and noise conversion ratios. The SESAM laser is found to show an excess noise conversion from the laser RIN to the laser phase noise due to the slow saturable absorber effect.